Creeping Clinical Attachment After Acellular Dermal Matrix Augmentation to Attain Root Coverage. Issue 2 (7th October 2019) - Changi, Khashayar Kordbacheh; Greenstein, Gary; Tarnow, Dennis; Royzman, Daniel; Kang, Philip
Abstract : Introduction: This case report documents root coverage after using an acellular dermal matrix (ADM) combined with a tunneling procedure. The photographs and objective clinical measurements are presented to document a gain of new clinical attachment and subsequent creeping attachment. Case Presentation: A 50‐year‐old male who demonstrated around 6 mm of recessions on the direct facial of teeth #6 through #11 had a root coverage procedure using an ADM. After 24 months, >90% of the recession defects at all sites were eliminated. It was noted that creeping clinical attachment began to appear 6 months after initial therapy on teeth #7 through# 11. Conclusion: The delayed creeping attachment seems to be due to the time necessary to vascularize the ADM and the rate of vascularization may vary with different thicknesses of inserted ADM.